Digital Branding and Revitalization, as an Effort to Improve the Image and Income of MSMEs in Blimbingsari Village, Banyuwangi Regency - Wafa, Ali; Angin, Ria; El Muhammady, Iffan Gallant (Institut Teknologi Nasional, Bandung, 2024)
The existence of Blimbingsari beach as a buffer tourism in the central Banyuwangi area, has decreased visitor interest every year. The decline is caused by 3 most pressing problems, including; 1) Unreasonable culinary selling prices; 2) Piles of beach garbage; and 3) Poor beach appearance/atmosphere. These problems have begun to threaten the people who depend on beach activities for their economy. Funding support provided by the Ministry of Education, through the PPK Ormawa 2023 program. Provide a commitment to empowerment, to prevent threats to the welfare of beach communities due to decreased visitor interest. Carried out for 4 months productively, using a Participatory Action Research (PAR) approach. Qualitatively, the beach community has shown positive behavioral changes. These changes are marked by; Equitable culinary selling prices; Routine beach cleaning activities; and supporting the revitalization of the beach appearance. These changes contribute to restoring interest in tourist visits, as evidenced by an increase in tourist ticket sales.